How to do a complete mesocolic excision and central vascular ligation. Issue 7 (8th June 2020) - Suhardja, Thomas Surya; Das, Atandrila; Rajkomar, Amrish KS; Smart, Philip; Heriot, Alexander G.; Warrier, Satish K.
Abstract : We describe an approach for complete mesocolic excision and central vessel ligation utilizing a robotic platform. We describe the steps in detail focusing on a superior mesenteric vein‐first approach.